A case study of sixth form secondary school students’ perceptions on participation in school-based extra-curricular activities at a co-educational, government secondary school in the Victoria Education District - Elcock, Tracey Georgiana (My University, 2017)
This qualitative case study investigated sixth-form secondary school students’ perceptions regarding participation in school-based extra-curricular activities at a co-educational, government secondary school in Trinidad and Tobago. It sought to gain a deeper understanding of the types, advantages, challenges and opportunities for improvement of school-based extra-curricular activities. Purposive sampling was used to select seven students who participated and did not participate in these activities. Data were collected through interviews. The students identified several advantages of participation such as skill development. Among the challenges enumerated were time management and finance.
Keywords: Perception; Case studies; Secondary school students; Student attitudes; Coeducational schools; Extracurricular activities; Trinidad and Tobago